Waste paper-based carbon aerogel supported ZIF-67 derived hollow NiCo phosphate nanocages for electrocatalytic oxygen evolution reaction. (10th October 2021) - Cui, Ce; Lai, Xiaoxu; Guo, Ronghui; Ren, Erhui; Qin, Wenfeng; Liu, Li; Zhou, Mi; Xiao, Hongyan
Abstract: Transition metal phosphates with hollow structure have attracted substantial attentions as high-performance electrocatalyst for oxygen evolution reaction (OER). However, these electrocatalytic materials need conductive carrier to realize efficient charge transfer and further improve the OER activity. In this work, ZIF-67 derived hollow NiCo phosphate nanocages supported by waste paper-based carbon aerogel (NCP@WPCA) was prepared as high-efficiency and stable electrocatalyst. Benefited from the enhanced electrochemical active surface area and fast gas emission, the NCP@WPCA catalyst exhibits superior OER activity with low overpotential of 351 mV at current density of 10 mA cm −2, along with good stability in alkaline solution. Additionally, the waste paper-based carbon aerogel as the carrier for electrocatalysts achieves low-cost waste reuse. Graphical abstract: Image, graphical abstract